Development of LMS and Z Score Growth References for Egyptian Children From Birth Up to 5 Years - El Shafie, Ali M.; El-Gendy, Fady M.; Allahony, Dalia M.; Hegran, Hossam H.; Omar, Zein A.; Samir, Mohamed A.; Kasemy, Zeinab A.; El-Bazzar, Ahmed N.; Abd El-Fattah, Mohamed A.; Abdel Monsef, Amir A.; Kairallah, Amir M.; Raafet, Hythem M.; et al. (Frontiers in Pediatrics, 2021)
Abstract Background: The Lambda – Mu- Sigma (LMS) and Z score methods are important for assessment of growth and nutritional status. In Egypt, there is a lack of this tool for monitoring growth in preschool children. Objective: To develop LMS and Z score growth references for assessment of growth and nutritional status for Egyptian children from birth up to 5 years. Methods: A total of 27,537 children (13,888 boys (50.4%) and 13,649 girls (49.6%)) from birth up to 5 years were included in a multistage cross sectional randomized study from different Egyptian geographic districts to create LMS and Z score references for weight, length/height and body mass index corresponding to age in addition to weight for length/height. Healthy term infants and children, exclusive breast feeding for at least 4 months and not suffering from any chronic diseases were included in this study. Children with dysmorphic features, preterm infants, admitted in neonatal or pediatric intensive care units and having any chronic diseases (hematological, cardiac, hepatic and renal) were excluded. In addition any health condition that affects child growth including nutritional disorders was also excluded. Un-paired t test was calculated to compare the means of weight for age, length/height for age, weight for length/height and BMI for-age z scores of the Egyptian and WHO reference values. Results: Through detailed tables and graphs, LMS and Z scores for weight for age, length/height for age, weight for length/height and BMI for age of both sexes were represented. Our findings showed no statistically significant difference between reference charts of WHO and Egyptian Z score charts (P>0.05). Conclusion: This study provides the first reference for Egyptian children from birth up to 5 years based on Z score tool for assessment the growth and nutritional status in various clinical conditions and research, also allows comparison with references of other countries.